TRANSFORMATION OF SHARIA FINANCIAL INSTITUTIONS THE CASE OF ACEH: POLITICS, STRATEGY AND IMPLEMENTATION - Kurniawan, Rahmad; Sukmana, Enriko Tedja; Dakhoir, Ahmad (FINANSIA : Jurnal Akuntansi dan Perbankan Syariah, 2023)
Aceh Special Region Government Authority which carried out mass transformation of conventional financial institutions in Aceh. Based on Aceh Qanun Number 11 of 2018 concerning Sharia Financial Institutions, conventional financial institutions are given 3 years from 2019-2022 to transform conventional financial institutions into Islamic financial institutions. The results of empirical-normative research, data sourced from interviews and observations, and sourced from normative data, namely Qanun Aceh Number 11 of 2018 concerning Sharia Financial Institutions. The approach used is legislation, case study approach, and conceptual approach. This research states that the transformation of financial institutions stems from the philosophy of culture and community life that adheres to the Quran and Sunnah. This philosophy is realized through strengthening legal politics in the form of Aceh Qanun Number 8 of 2014 and Aceh Qanun Number 11 of 2018.